Autonomous Chemotactic Light‐Emitting Swimmers with Trajectories of Increasing Complexity. (4th December 2020) - Pavel, Ileana-Alexandra; Salinas, Gerardo; Perro, Adeline; Kuhn, Alexander
Abstract : Miniaturized autonomous swimmers have become more and more important in many areas of research due to various fields of use, ranging from biomedical to environmental tasks. Precise and predictable control of their trajectories is a key ingredient for increasing their application potential. This can be typically achieved by using external forces such as magnetic or electric fields. An interesting alternative is to use intrinsic features of the swimmers, which allow them to exhibit chemotaxis. Such a built‐in "intelligence" enables more complex trajectories, relying on mechanisms that can be considered very basic analogs of decision‐making processes. Herein, autonomous light‐emitting chemoelectronic swimmers are presented that are able to navigate along trajectories with increasing complexity. Their decision‐making capacities are characterized by recording the light emitted along their path by a fully integrated light‐emitting diode. Chemotaxis is found to be the main driving force behind their behavior, allowing envisioning such systems for solving complex maze patterns. Abstract : Self‐propelled chemoelectronic swimmers follow complex chemical gradients in maze‐type structures. The simultaneous integrated light emission allows easy tracking of the trajectories resulting from successive decision‐making processes.